Green Organizational Culture as an Emerging Tren : A Bibliometric Analysis - Rosyanti, Daisy Marthina; Dewanti, Mentari Clara; Khoirotunnisa, Fani (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : Conducting a literature review to examine the development of literature from the green culture variable so that a visual mapping is obtained that describes the interrelated relationship between green culture and environmental performance and other variables in several industrial sectors. Methode : This study employs a quantitative approach, utilizing time series data from the past decade along with bibliometric analysis. From the patterns and trends visualized, it can be known the relationship or correlation between various related factors. Research Finding : Organizational culture still dominates as a fundamental aspect of green organizational performance, although recent trends point to the broader evolution of the concept of